O MALTE DE CEVADA COMO FONTE DE AMILASES: HIDRÓLISE DOS AMIDOS DE MANDIOCA E BATATA-DOCE E FERMENTAÇÃO ALCOÓLICA DOS MOSTOS OBTIDOS - Luz, Felipe Staciaki da (2021)
Barley malt was evaluated as a source of amylolytic enzymes to hydrolyze cassava and sweet potato starches, in order to develop cleaner and cheaper ethanol production methodologies. The hydrolyses were carried out with two types of catalyst: the milled malt and the enzymatic extract of the malt. The two types of malt were also compared (Pilsen and Pale Ale). Hydrolyses with milled malt were carried out at concentrations of 5, 10 and 15% (w/w) and with cassava starch and sweet potato flour at a concentration of 10% (w/V). The enzymatic extract was used at the concentration of 0.5, 1.0 and 1.5 %(V/V) for the same concentration of starch and flour. For both types of starch, the enzymatic extract proved to be more efficient in hydrolysis and was chosen to continue the work. The hydrolysis of starches was optimized with a central rotational composite design 22. The hydrolysis of cassava starch presented an optimum condition at 2.93% (w/V) of starch and 3.68 %(V/V) of enzymatic extract Pilsen malt. For the hydrolysis of sweet potato starch, the optimum condition was 2.93% (w/V) of sweet potato flour and 8.09 %(V/V) of enzymatic extract of Pilsen malt. No significant difference was observed between Pilsen malt and Pale Ale in starch hydrolysis. For hydrolyzed cassava starch, the ethanol content obtained by alcoholic fermentation under optimized conditions was 8.17 ± 2.11 g L-1 for Pilsen malt and 7.01 ± 0.25 g L-1 for Pale Ale malt. In the case of hydrolyzed sweet potato starch, the levels for Pilsen and Pale Ale malts were 7.13 ± 0.32 g L-1 and 6.92 ± 0.0021 g L-1, respectively. The test of the effect of temperature variation showed that it did not contribute significantly to the levels of reducing sugars and ethanol obtained. Spectroscopy analysis in the infrared region by Fourier transform (FTIR) proved that ethanol was obtained as the main product of alcoholic fermentation, both from cassava starch and sweet potato flour.